El mercado de servicios complementarios en el sector eléctrico peruano: evolución normativa y desafíos - Calderón Rojas, Ximena (Pontificia Universidad Católica del Perú, 2025)
This article analyzes the regulatory evolution and regulatory challenges associated with the implementation of Complementary Services in the Peruvian electricity sector, in the context of the recent modification of Law 28832 and taking into account the Chilean comparative experience. In such manner, the current conditions of the regulatory framework and the need to introduce incentives that promote the participation of new actors are examined, especially given the increase in the penetration of intermittent renewable energies.

Este artículo analiza la evolución normativa y los desafíos regulatorios asociados a la implementación de los Servicios Complementarios (SSCC) en el sector eléctrico peruano, en el contexto de la reciente modificación de la Ley 28832 y tomando en cuenta la experiencia comparada chilena. De esta manera, se examinan las condiciones actuales del marco regulatorio y la necesidad de introducir incentivos que promuevan la participación de nuevos actores, especialmente, ante el aumento de la penetración de energías renovables intermitentes.
The market for complementary services in the Peruvian electricity sector: regulatory evolution and challenges
Keywords: Complementary Services; Regulation; Renewable energies; Comparative experience; Participation of new actors; Servicios Complementarios; Regulación; Energías renovables; Experiencia comparada; Participación de nuevos actores; https://purl.org/pe-repo/ocde/ford#5.05.01